Platform capitalism and expansion of wholesale retailers in the Porto Alegre City-region, Brazil - Soares, Paulo Roberto Rodrigues; Corrêa, Gabriel (Geografares, 2026)
The research analyses the transformations and the socioeconomic and socio-spatial repercussions resulting from the expansion of self-service wholesale stores (called “atacarejos”) in the Porto Alegre city-region (RS, Brazil). We investigate the transition from the post-Fordist accumulation regime toward “platform capitalism,” and the interactions between these “geographical objects” and their dynamics, and the productive and logistical restructuring associated with the growing financialization, flexibilization, and platformization of labor and consumer markets in the city-region. Theoretically, we engage with the debate and research about economic and metropolitan restructuring and the configuration of new socio-spatial logics. Methodologically, we use socioeconomic data and map the units of the main national and international distribution networks and its logistics centers in the study area. Finally, we discuss role of wholesale retailers in the metropolitan metamorphosis involving Porto Alegre city-region and conclude that it is increasingly inserted in global flows and networks of circulation of goods, capital, and information.